2021
DOI: 10.1186/s13041-021-00873-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular motor KIF3B in the prelimbic cortex constrains the consolidation of contextual fear memory

Abstract: Molecular and cellular mechanisms underlying the role of the prelimbic cortex in contextual fear memory remain elusive. Here we examined the kinesin family of molecular motor proteins (KIFs) in the prelimbic cortex for their role in mediating contextual fear, a form of associative memory. KIFs function as critical mediators of synaptic transmission and plasticity by their ability to modulate microtubule function and transport of gene products. However, the regulation and function of KIFs in the prelimbic corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…One of the molecular mediators of spine density within the PL is a molecular motor protein (KIFs). In this study, KIF3B was upregulated 1 hour after fear conditioning, and shRNA-mediated knockdown of KIF3B led to an increase in spine density [82]. An increase in spine density suggests that prefrontal neurons are more responsive to CS cues.…”
Section: Synaptic Plasticity Induced By Fear Memory Consolidationmentioning
confidence: 50%
“…One of the molecular mediators of spine density within the PL is a molecular motor protein (KIFs). In this study, KIF3B was upregulated 1 hour after fear conditioning, and shRNA-mediated knockdown of KIF3B led to an increase in spine density [82]. An increase in spine density suggests that prefrontal neurons are more responsive to CS cues.…”
Section: Synaptic Plasticity Induced By Fear Memory Consolidationmentioning
confidence: 50%
“…Specific alterations in transcription 1 3 , localized translation 4 , 5 , and axonal transport 6 9 lead to the creation of new synapses and the modification of existing ones 10 , 11 . These are widely recognized processes responsible for the establishment of long-term memory (LTM).…”
Section: Introductionmentioning
confidence: 99%
“…Given the highly polarized architecture of neurons, with the soma communicating with synapses through axons and extensive dendritic arbors, it is likely that soma-synapse communication is essential for synapse maintenance. Several studies, including our own, have demonstrated that long-distance delivery of gene products from the soma to the synapse via molecular motor proteins along microtubule tracks (Yamada et al, 1970) ensures proper synapse function and plasticity (Puthanveettil et al, 2008; Puthanveettil et al, 2013; Liu et al, 2014; Swarnkar et al, 2018; Swarnkar et al, 2021; Joseph et al, 2021; Panayotis et al, 2015; Guedes-Dias & Holzbaur, 2019). Kinesin mediates anterograde transport to deliver proteins, RNAs, and organelles to synapses (Saxton & Hollenbeck, 2012; Guillaud et al, 2020; Maday et al, 2014), while dynein/dynactin-facilitated retrograde transport is crucial for cellular signaling, material recycling, and neuronal homeostasis (Schwartz, 1979; Yamashita, 2019; Guedes-Dias & Holzbaur, 2019).…”
Section: Introductionmentioning
confidence: 99%